THE ROLE OF MINISTRAL AFFAIRS BODIES IN PREVENTING DOMESTIC VIOLENCE AGAINST WOMEN AND CHILDREN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The scientific article provides a brief analysis of the judicial and legal reformcarried out in the Kyrgyz Republic in the area of prevention and prevention of domestic violence.In addition, factors that hinder the effective fight and prevention of domestic violence by internalaffairs bodies are reflected.
Keywords: judicial reform; codes and laws, temporary protective order, victims of domestic violence, entities providing protection from domestic violence.